2019
DOI: 10.1051/0004-6361/201935364
|View full text |Cite
|
Sign up to set email alerts
|

Ground-based optical transmission spectrum of the hot Jupiter HAT-P-1b

Abstract: Context. Time-series spectrophotometric studies of exoplanets during transit using ground-based facilities are a promising approach to characterize their atmospheric compositions. Aims. We aim to investigate the transit spectrum of the hot Jupiter HAT-P-1b. We compare our results to those obtained at similar wavelengths by previous space-based observations. Methods. We observed two transits of HAT-P-1b with the Gemini Multi-Object Spectrograph (GMOS) instrument on the Gemini North telescope using two instrumen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Lightcurves are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc. u-strasbg.fr/viz-bin/cat/J/A+A/641/A158 Casasayas-Barris et al 2018Seidel et al 2019;Chen et al 2020), studies at lower resolution can give us information about the continuum of the exoplanet spectrum (e.g., Rackham et al 2017;May et al 2018May et al , 2020Bixel et al 2019;Todorov et al 2019;Weaver et al 2020). Moreover, groundand space-based low-resolution transmission spectroscopy allows us to probe for potential broad absorption line wings and slopes caused by hazes in the atmosphere of Jovian-like transiting planets.…”
Section: Introductionmentioning
confidence: 99%
“…Lightcurves are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc. u-strasbg.fr/viz-bin/cat/J/A+A/641/A158 Casasayas-Barris et al 2018Seidel et al 2019;Chen et al 2020), studies at lower resolution can give us information about the continuum of the exoplanet spectrum (e.g., Rackham et al 2017;May et al 2018May et al , 2020Bixel et al 2019;Todorov et al 2019;Weaver et al 2020). Moreover, groundand space-based low-resolution transmission spectroscopy allows us to probe for potential broad absorption line wings and slopes caused by hazes in the atmosphere of Jovian-like transiting planets.…”
Section: Introductionmentioning
confidence: 99%
“…Ground-based observations have also proved to be successful in correcting for the telluric effects by applying the differential spectrophotometry method. These observations are mostly carried out with multi-object spectrographs mounted on large telescopes, for example, FORS2 on the Very Large Telescope (VLT; Lendl et al 2016;Nikolov et al 2016;Sedaghati et al 2016), OSIRIS on the Gran Telescopio Canarias (Chen et al 2017a;Murgas et al 2017), GMOS on the Gemini telescope (Gibson et al 2013;Todorov et al 2019), IMACS on the Magellan telescope (Rackham et al 2017;Espinoza et al 2019), and MODS on the Large Binocular Telescope (LBT; Mallonn & Strassmeier 2016). These ground-based observations provide transmission spectra in the optical wavelength range that cover features such as Na/K (Sing et al 2012;Lendl et al 2017;Chen et al 2018;Nikolov et al 2018;Pearson et al 2019), TiO/VO (Sedaghati et al 2017), and the Rayleigh-scattering slopes (Nikolov et al 2015;Parviainen et al 2016;Kirk et al 2017;Chen et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Clouds and hazes are best characterised in the optical, where they are not degenerate with molecular abundances, and work with LRG-BEASTS and other surveys have shown that ground-based observations can provide optical transmission spectra with precision comparable to space-based telescopes (e.g. Todorov et al 2019;Alderson et al 2020;Carter et al 2020;Weaver et al 2021). With the upcoming launch of the James Webb Space Telescope (JWST), which will provide precise transmission spectra across the near-and mid-infrared, the measurement of optical transmission spectra will be crucial for combined analyses to break degeneracies due to clouds and hazes and measure accurate atmospheric abundances.…”
Section: Introductionmentioning
confidence: 99%